Assessment of allelopathic potential of goniothalamin allelochemical from Malaysian plant Goniothalamus andersonii J. Sinclair by sandwich method - Raihan, I.; Miyaura, Rie; Baki, Bakar; Fujii, Yoshiharu (International Allelopathy Foundation, 2019)
We evaluated the allelopathic potentials of 145 plant species collected from several locations in Malaysia using the sandwich method. Among them, the bark of Goniothalamus andersonii J. Sincl. proved most inhibitory to radicle growth of lettuce seedlings, followed by leaves of Ageratum conyzoides L. (Asteraceae), Amaranthus spinosus L. (Amaranthaceae) and Goniothalamus longistipites Mat Salleh (Annonaceae) bark. Goniothalamin was identified as the potent allelochemical from the bark of G. andersonii. The EC50 value of goniothalamin against the growth of lettuce radicles was 50 µmol L-1. The total activity of goniothalamin was maximum on the growth of lettuce than other allelochemicals [6-O-(4’-hydroxy-2’-methylene-butyroyl)-1-O-cis-cinnamoyl-β-D-glucopyranose (BCG), L-3,4-dihydroxyphenylalanine (L-DOPA) and 1-O-cis-cinnamoyl-β-D-glucopyranose (cis-CG)].